PENETAPAN PRIORITAS PENILAIAN KARYAWAN PADA GOLDEN VIEW HOTEL BATAM: ESTABLISHMENT OF EMPLOYEE ASSESSMENT PRIORITIES AT THE GOLDEN VIEW HOTEL BATAM - Albertus Laurensius Setyabudhi; Eci Ermawati (Engineering and Technology International Journal, 2020)
Golden View Hotel is one of the 4-star hotels in the city of Batam. The hotel is facing the problem of decreasing the rating of the housekeeping division, where the managers want the desired housekeeping criteria. There are 4 factors that are considered the most important by distributing the questionnaire then the results are calculated through AHP (analytical hierarchy process) calculations to find the priority weight value which has been obtained for the Behavior factor weight with a total of 0.51 which has 4 variables, for the knowledge factor weight a total of 0.33 where has 4 variables, for the ability factor weight with 0.16 which has 4 variables. So the author can propose that the standard assessment of the Golden View Hotel company will be a benchmark for the desired criteria for housekeeping employees.